Analisis Konstitusional Larangan Rangkap Jabatan Wakil Menteri Di Indonesia - Muhammad Safaat Gunawan; Karsa, Pipih Ludia; Pradana, Syafa'at Anugrah; Mirdedi; Eki Furqon (JURNAL SULTAN: Riset Hukum Tata Negara, 2025)
The phenomenon of Deputy Ministers holding concurrent positions as commissioners or supervisory board members in State-Owned Enterprises (SOEs) reveals a serious problem in Indonesian constitutional practice, namely the lack of synchronization between legal norms and political behavior. Various laws and regulations, such as Law No. 39 of 2008 on State Ministries, Law No. 25 of 2009 on Public Services, and Law No. 19 of 2003 on SOEs, explicitly and imperatively prohibit public officials, including Deputy Ministers, from holding positions that have the potential to cause conflicts of interest. This provision is reinforced by Constitutional Court Decisions No. 79/PUU-IX/2011 and No. 80/PUU-XVII/2019, which confirm that Deputy Ministers are part of the government cabinet and are therefore subject to the same restrictions on concurrent positions as Ministers. This study uses a normative juridical approach with legislative, conceptual, and case analysis to examine the clarity of the norm prohibiting concurrent positions and the direction of legal reform needed. The results of the study confirm that the prohibition on holding multiple positions is binding and must be enforced in accordance with the mandate of the law and the decision of the Constitutional Court. In addition, there is a tendency for a constitutional crisis to occur in the government. Therefore, regulatory reforms are needed to reinforce this prohibition at the legislative level and limit the executive's authority in determining public positions. Keywords : Dual roles, Regulatory reform, Constitutional crisis.